(untitled) (Archives of Pediatrics of Uruguay, 2022)
Introduction: around 30% of childhood diseases are caused by social, environmental and family issues, as well as by life conditions, family dynamics and exposure to toxic substances. Understanding the characteristics of the pediatric population assisted at this Health Center, will help us identify health-threatening factors. Objectives: Describe the clinical and epidemiological characteristics of the population under 15 years of age assisted at Badano Repetto Health Center between 2020 and 2021. Understand the different variables that could influence this population´s health. Identify the link between family, social and cultural variables and neurological development at different ages. Methodology: descriptive, retrospective cross-sectional study. Convenience sampling of 15% of the total number of children and adolescents under 15 years of age, assisted at the Health Center from 10/01/2020 to 3/31/2021. Variables: children: sex, age, perinatal history, growth and neurological development, health checkups, vaccines, school attendance, extracurricular activities. Parents: age, education, psychoactive substance use, pathological background, job, prison. Family and household: parent`s marital status, domestic violence history, cohabitants, housing characteristics, basic household services, government aids, community interventions. Data source: medical records and telephone conversations. Data was recorded on template charts. We used results in absolute and relative frequencies, and their measures of central tendency measures and their range, Chi-square test or Fisher´s exact test. Significance level 0,05. Epi Info Program, version 7.2. Informed parent and adolescent consent. Approved by the CHPR Ethics Committee. Results: out of the 2826 patients under 15 years of age assisted at the clinic, we included 426 (15%), but only 263 (62%) were analyzed, since we were not able to reach 163 (38%) by phone. 52% were female. The average age was 4 years of age (5 days-14 years old). 69% of children were under 5 years old. 83% of patients had adequate number of checkups and 91% had an updated vaccination chart. 12% were overweight/obese. Neurodevelopment was adequate in 93% of those under 5 years of age, and 56% of those over 5 years of age. Regarding those with neurodevelopmental difficulties and over 5 years of age, 46% had learning disabilities, 39% had behavioral disorders, 32% language disorders, 10% intellectual deficit. 56% attended school, all of them public schools. For those who did not attend school, 4 of them were old enough to attend mandatory school (6, 7, 9 and 10 years of age). 20% of the children and adolescents had failed at least one year in school or high school. Perinatal findings: 14% of mothers had substance use during pregnancy, mainly tobacco and cocaine base paste. 85% of them had been born to term, 10% had neonatal depression 15% of children/adolescents had been exposed to domestic violence and 32% of them (12/38) had one parent with psychoactive drug use at home. 21% of children/adolescents exposed to domestic violence had a learning disability. 8% had at least one parent who did not finish primary school and 28% who did not finish middle school. Statistically, a significant link was found between psychoactive substance use, declared by one or both parents, and domestic violence. No statistically significant link was found between neurodevelopmental difficulties and domestic violence. Conclusions: these findings show a socially and economically vulnerable population, parents with little formal education, higher cocaine paste base use during pregnancy than the national statistics and 15% of children/adolescents exposed to domestic violence, even though they a high number of them had received their health checkups. The biggest strength shown by this study is the importance of maintaining a good bond with these families, who showed a high level of commitment with the health center. This leads us to prioritize health prevention and promotion as a valuable tool to achieve health quality standards for these children and adolescents. New studies, using other methodologies, will be necessary to analyze this data.